2010
DOI: 10.1007/s12020-010-9418-1
|View full text |Cite
|
Sign up to set email alerts
|

Loss-of-function of SHARPIN causes an osteopenic phenotype in mice

Abstract: SHARPIN is a novel protein thought to interact with SHANK family and is widely expressed in multiple tissues/cells, including osteoblasts and osteoclasts. Loss-of-function of Sharpin develops the chronic proliferative dermatitis mutation (CPDM) in mice as well as a severe inflammation in other organs. The actual function of SHARPIN is poorly understood. Our aim was to determine the functional roles of SHARPIN in bone metabolism by using CPDM mice. The skeletal phenotypes were determined by peripheral quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 21 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…Upon proinflammatory cytokine stimulation, LUBAC linearly ubiquitinates NEMO and RIP1, and induces canonical NF‐κB activation (Tokunaga et al , 2009; Gerlach et al , 2011; Ikeda et al , 2011; Tokunaga et al , 2011). Recent studies showed that LUBAC regulates the interferon production pathway (Inn et al , 2011), the genotoxic stress response (Niu et al , 2011), tumour metastasis (Tomonaga et al , 2012), osteogenesis (Xia et al , 2011) and innate immunity (Damgaard et al , 2012), highlighting the physiological significance of LUBAC‐catalysed linear ubiquitination in a wide variety of NF‐κB‐related cellular responses.…”
Section: Introductionmentioning
confidence: 99%
“…Upon proinflammatory cytokine stimulation, LUBAC linearly ubiquitinates NEMO and RIP1, and induces canonical NF‐κB activation (Tokunaga et al , 2009; Gerlach et al , 2011; Ikeda et al , 2011; Tokunaga et al , 2011). Recent studies showed that LUBAC regulates the interferon production pathway (Inn et al , 2011), the genotoxic stress response (Niu et al , 2011), tumour metastasis (Tomonaga et al , 2012), osteogenesis (Xia et al , 2011) and innate immunity (Damgaard et al , 2012), highlighting the physiological significance of LUBAC‐catalysed linear ubiquitination in a wide variety of NF‐κB‐related cellular responses.…”
Section: Introductionmentioning
confidence: 99%
“…Even considering the anatomic and biological differences between human and mouse [10], normal keratinocyte differentiation [11], Th2 but not Th1 inflammation [12], and different malfunctions of involved organs suggested Sharpin cpdm mice do not indeed resemble human psoriasis. Beside dermatitis, hepatosplenomegaly, pneumonia, lymphadenitis, upper gastrointestinal eosinophilic inflammation, and osteopenic phenotype are also severe symptoms in Sharpin cpdm mice [1315]. Persistent eosinophilia, multisystem eosinophil infiltration, aberrant CD3 − CD4 + cells, equivalent sex ratio, and Th2-type inflammation suggested Sharpin cpdm mutant may be more likely as a mouse model for the lymphocytic variant of hypereosinophilic syndrome (LHES) [14].…”
Section: Introductionmentioning
confidence: 99%
“…6 A ), induces to the development of chronic proliferative dermatitis mutations ( Cpdm ) and an osteopenic phenotype in mice. ( 72 ) This phenotype was solely explained by impaired bone formation without affecting osteoclastogenesis. ( 73 ) We observed a similar phenotype in the Shank2 −/− mice due to decrease in osteoblastogenesis, whereas osteoclastogenesis remains unaffected.…”
Section: Discussionmentioning
confidence: 99%